PROMOSI JABATAN: PERAN KOMITMEN DAN KOMUNIKASI ORGANISASI DENGAN PRESTASI KERJA SEBAGAI VARIABEL INTERVENING - Surya, Leonardus; Sanggarwati, Diah Ayu; Lazuardi, Sofyan; Khakim, M. Azizul (Media Mahardhika, 2025)
Human Resources (HR) is one of the important factors that cannot be separated from an organization. The object of this research is PT Jawa Pos which is a print media company in Indonesia, competition in the printing world today requires commitment, communication and good work performance to help make advertising easier and more efficient. This study aims to determine the promotion of the role of commitment and communication and organization with work performance as an intervening variable in the advertising division of PT Jawa Pos Surabaya. The sampling technique in this study was a total of 80 employees. Data collection techniques using questionnaires. Data analysis uses data quality test, classical assumption test, hypothesis test, and path analysis. The results concluded that organizational commitment affects promotion in the Advertising Division of PT Jawa Pos Surabaya. Organizational commitment affects job performance in the Advertising Division of PT Jawa Pos Surabaya. Organizational commitment has no effect on promotion through job performance in the Advertising Division of PT. Jawa Pos Surabaya. Work achievement affects job promotion in the Advertising Division of PT Jawa Pos Surabaya. Organizational communication affects job promotion in the Advertising Division of PT. Jawa Pos Surabaya. Organizational communication affects job performance in the Advertising Division of PT Jawa Pos Surabaya. Organizational communication affects job promotion through job performance in the Advertising Division of PT. Jawa Pos Surabaya